Optimal transportation and spatial integration of regional palm oil markets in Nigeria (2016)
"The poor quality of transportation infrastructure in Nigeria impacts negatively on the competitiveness of palm oil. This leads to increased inter-regional transportation cost, delayed time of arrival to the destination and lowered transaction efficiencies in the distribution chains. Primary and secondary data were used. Random sampling technique was used to collect data from 276 distributors in main palm oil markets. Data were analyzed using linear programming and Ravallion model at 0.05 a-level. Results of the data analyzes show that average cost of transporting palm oil from the production market to the consumption market was N5,831.9 per MT. Observed transportation cost was N60,724,830.5 while the optimal cost was N44,003,500.30 indicating a 38.0% reduction in total cost of transportation. Highest optimal allocations to the destination markets were Owerri-Jos (133,500 MT), Ondo-Lagos (107,200 MT) and Port Harcourt-Kano (82,000 MT) at minimum transportation cost of N5,750, N4000.7and N6500.0 per MT respectively. Two lag periods were identified signifying that it takes about 1-2 months for price information to spread across the markets by the model. Six of the 27 market pairs exhibited high short-run market integration for both lag periods with Port Harcourt-Abuja market pail: indicating the highest (0.1 and 0.004). The lowest short-run market integration was recorded in Ondo-Minna market pair indicated by 1.4 and 17.4 respectively. Policies that will enhance redistribution of palm oil supply between producing and consuming regions should be pursued. "